A National Assessment of the Health and Safety of Emergency Medical Services Professionals. (28th November 2016) - Bentley, Melissa A; Levine, Roger
Abstract: Objectives: The objectives were to assess changes in (1) health and physical fitness, (2) the prevalence of selected health problems, (3) risk behaviors, (4) ambulance safety issues, and (5) the preparedness of Emergency Medical Services (EMS) professionals. In addition, the incidence of patient-initiated violence directed toward EMS personnel and associated factors were assessed. Methods: Data were obtained from a sample of nationally certified EMS professionals via annual questionnaires between 1999 and 2008. Stratification was based upon national certification level, self-reported race, and experience level. Weighted percentages, averages for continuous variables, and 95% confidence intervals (CIs) were calculated. Significant changes over time were noted by lack of CI overlap. Results: The proportion reporting "excellent" health declined significantly from 1999 (38.5%) to 2008 (32.2%). High rates of sleeping problems (20%-27%), back problems (20%-24%), and hearing problems (7%-10%) were reported as having occurred in the past year. These rates remained constant over time. As a result of sleepiness, 8.0% of nationally certified EMS professionals reported difficulty in driving an emergency vehicle for short distances and 17.5% reported difficulty in driving long distances. The proportion of daily tobacco smokers significantly declined from over one-third (35.3%) to about one-fifth (20.3%). The proportion of providers who had ever been involved in an ambulance crash increased slightly from 2004 (14.5%) to 2008 (15.8%). In 2000, the majority of EMS professionals reported that they and/or their partner had been assaulted by a patient. Finally, there was a significant decrease in the amount of training time devoted to the recognition of biological, chemical, and nuclear (BCN) threats, use of personal protective equipment (PPE), and treatment and management of patients exposed to BCN from an average from 8.4 hours in 2003 to 6.2 hours in 2008. Conclusions: The overall health and physical fitness of EMS professionals as well as their health problems, risk behaviors, ambulance safety, and patient-initiated violence in the prehospital emergency setting are areas of concern for the nation's emergency medical system. The prevalence of these problems and overall health and physical fitness has shown little or no improvement from 1999 to 2008. MA Bentley, R Levine .A national assessment of the health and safety of Emergency Medical Services professionals .Prehosp Disaster Med .2016 ;31 (Suppl.1 ):s96 –s104 .